1
$\begingroup$

$$9a_{n} = 6a_{n-1}-a_{n-2}, a_{0}=6, a_{1}=5$$

So

$$x^n = (6x^{n-1}-x^{n-2})\div9$$

thus

$$[x^2 = (6x-1)\div9] \equiv [x^2 - \frac{2}{3}x + \frac{1}{9} = 0], x=\frac{1}{3}$$

also

$$a_{2}=\frac{8}{3}, a_{3}=\frac{31}{27}$$

How do I plug in that x/root to solve for the given recurrence relation?

I tried

$$9a_{n} = 6(\frac{1}{3})^{n-1} - (\frac{1}{3})^{n-2}$$

which for n=1 gives 5... which is correct, for a_1 though, not 9a_1? So that's not right.

$\endgroup$
0
$\begingroup$

Since $a_n=c\left(\frac{1}{3}\right)^n+dn\left(\frac{1}{3}\right)^n$, $a_0=2\implies c=6$ and $a_1=5\implies d=9$, so

$\displaystyle a_n=\frac{6}{3^n}+\frac{9n}{3^n}=\frac{2+3n}{3^{n-1}}$

$\endgroup$
6
  • $\begingroup$ thank you but what is this d. $\endgroup$ – user163831 Dec 3 '14 at 21:06
  • $\begingroup$ c and d are arbitrary constants, and then we can use $a_0$ and $a_1$ to solve for them. $\endgroup$ – user84413 Dec 3 '14 at 21:07
  • $\begingroup$ Since there is a repeated root, the general solution to the recurrence has the form $a_n=c(r^n)+dn(r^n)$ where c and d are constants and r is the repeated root. $\endgroup$ – user84413 Dec 3 '14 at 21:09
  • $\begingroup$ awesome thanks. that's only for repeated root cases though? so like if there were 2 distinct roots i wouldn't follow this formula? $\endgroup$ – user163831 Dec 3 '14 at 21:11
  • $\begingroup$ I am just canceling a common factor of 3 on the top and bottom after combining the two fractions. $\endgroup$ – user84413 Dec 3 '14 at 21:23
0
$\begingroup$

Here are the steps $$ a_{0}=6 $$ $$ a_{1}=5 $$ $$ 9a_{n} = 6a_{n-1}-a_{n-2} $$ Lets rewrite this recurrence as $$ a_{n} = \frac69a_{n-1}-\frac19a_{n-2} $$ $$ a_{n} = \frac23a_{n-1}-\frac1{3^2}a_{n-2} $$ Now let's multiply by $3^n$ $$ 3^0a_{0}=3^06=6 $$ $$ 3^1a_{1}=3^15=15 $$ $$ 3^na_{n} = 2\cdot 3^{n-1}a_{n-1}-3^{n-2}a_{n-2} $$ Let $S_n=3^na_n$, then $$ S_0=6 $$ $$ S_{1}=15 $$ $$ S_n= 2S_{n-1}-S_{n-2} $$ It follows that $$ S_n= S_1n-S_0(n-1)=9n+6=3(3n+2) $$ Therefore

$$ a_n=\frac{3(3n+2)}{3^n}=3^{1-n}(3n+2) $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.